An Analysis of the Relationship between Attention-Deficit Hyperactivity Disorder and Unnmad - Patel, Harun; Daberao , Sandip; Changle, Sunil; Khawale , Deepak (International Research Journal of Ayurveda & Yoga, 2025)
One kind of mansik - vyadhi, the most prevalent type of mental illness, is unnmad. Attention-deficit hyperactivity disorder (ADHD), or attention deficit hyperactivity disorder, and unnmad may be connected. In the contemporary period, the number of children affected by psychosocial disorders on a daily basis has increased in pediatric clinics; Attention-deficit hyperactivity disorder is one such disorder. This disorder is brought on by a decrease in self inhibitory capacity, an increase in distractibility and difficulties maintaining focus, poor impulse control, motor hyperactivity, and motor restlessness, among other factors. It is the most prevalent neurological condition affecting children. Many of these issues are momentary in nature and frequently go unrecognized. That being said, about half of the children who are referred to child psychiatrists, behavioral pediatricians, and neurologists have attention-deficit/ hyperactivity disorder. It is typified by inattention, which includes diminished self-inhibitory capacity, increased distractibility, and trouble maintaining focus, as well as motor hyperactivity and restlessness. It was discovered that 11.32% of elementary school students have ADHD. In Ayurveda, all mental illnesses are categorized under the term “manasvyadhi.” The one line that captures the essence of Unnmada’s distinct individuality is “unnmadam punah mano buddhi sadnya dhyan smruti mati bhakti shil chesta acharvibhram vidhyat.[1] Because of the vitiation of dhee, dhriti, and smriti, which results in an imbalance of kala and karma, the senses are unable to properly connect with their goals (Asatmendriyartha samyoga), which leads to impulsivity, hyperactivity, and inattention.[2] It was discovered that 11.32% of elementary school students have attention-deficit hyperactivity disorder (ADHD).[3] Although ADHD and Unmada are not specifically related in Ayurveda, their symptoms point to a possible relationship.